Alkali-Activated Concrete Via Oven and Microwave Radiation Curing - Tashima, M. M. [UNESP]; Payá, J.; Borrachero, M. V.; Monzó, J.; Soriano, L. (Elsevier, 2021)
This chapter presents a comprehensive review on alkali-activated concrete via oven and microwave radiation curing, where the influences of oven and microwave radiation curing on the alkali-activated concrete (AAC) were investigated with respect to their physical, mechanical, and chemical properties. The microwave radiation curing outperformed oven curing owing to its better and uniform distribution of heat than conventional methods as well as its significantly shorter curing duration, resulting from the triggering of the break of Si-O and Al-O bonds so that a better dissolution of materials can be achieved. However, some microcracks could occur on these AAC, hence a careful curing regime should be adopted when microwave curing technique is applied in practice.
Keywords: Alkali activation concrete; Compressive strength; Microstructures; Microwave radiation curing; Oven curing